Muhammad Iqbal’s prediction on the modern science: a response to the scientific worldview - Ali, Mohd Mumtaz; Hasan, Md Maruf (Iqbal Chair Bahria University, Pakistan, 2025)
The inherent crisis of faith due to modern science was prevalent in Western literature during the time of Muhammad Iqbal. After conducting extensive research on Western philosophy, Muhammad Iqbal recognized its intrinsic contradictions and forewarned future Muslim generations. In the 21st century, we are witnessing the rise of New Atheism within Muslim societies. With the development of modern science, there is a growing inclination toward the scientific worldview. Muslim youth are not excluded since their education systems still lack the integration of Islamic knowledge. Muhammad Iqbal’s philosophical thought on ‘Khudi/Self’ is extremely relevant and necessary for internalizing Islamic values and rebuilding confidence in the Islamic worldview among Muslim students. This research analyzes Iqbal’s philosophical poem, The Secrets of the Self, to extract its core message for restoring Muslim students' conviction in the Quranic worldview. This article employs a qualitative research methodology, utilizing content analysis to examine Iqbal’s thoughts on the modern crisis arising from the dominance of science. The findings indicate that Iqbal unequivocally affirms the Tawhidic worldview (“There is no God except Allah”) as the ultimate solution for humanity. This research suggests that Muslim students can adopt Muhammad Iqbal’s Tawhidic paradigm as a response to the scientific worldview propagated by New Atheism